Descriptive study of the traditional goat production in the mixteca and central valleys regions of Oaxaca, Mexico - Ortiz-Morales, Oscar; Arias-Margarito, Ladislao; Lopéz Ojeda, José Carlos; Soriano-Roble, Ramón; Almaraz-Buendía, Isaac; Ramírez-Bribiesca, Efrén (Ecosistemas y Recursos Agropecuarios, 2021)
The traditional knowledge of goat farmers in Oaxaca has been inherited from generation to generation for nearly 500 years. This study describes the traditional goat production with emphasis on its social, ecological, and genetic resources in the Mixteca (MX) and Central Valleys (VC) regions of Oaxaca. Ethnography was the method used to assess the complexity of the signiﬁcant phenomena for goat farmers. The ordering of information was systematized according to a social and cultural context, management of genetic resources, ecological context, and importance for livelihoods. Main results show that goats are handled by 50- year-old farmers. There are two production strategies: transhumant and non-transhumant. Four goat genotypes are described: Pastoreña, Chinchorrera/Corralera, Fina, and Criolla. In VC, goats are exploited mainly for milk production. In the MX, the objective is meat production. Different grazing practices are used, which indicates a clear adaptation of goats to changing environmental conditions. Also, movement of goat herds make use of the availability of forage according to the season of the year. It was concluded that traditional goat production in MX and VC is heterogeneous. Besides, transhumant, and non-transhumant productions coexist and are classiﬁed as a primary or complementary activity, respectively. They are characterized by the workforce and type of goat used, as well as the number of animals per herd, the type of handling during grazing, and the production target.